Achievement of wrestlers different continents at the Olympic Games - Apoikia, R.; Tarakanov, B.; Shevtsov, A. (International Journal of Wrestling Science, 2013)
The paper presents the results of a study of levels of achievements in sport wrestlers from different continents in the Olympics. This level of analysis is required to determine the dynamics and prospects for the development of wrestling as substantiated evidence of its popularity in the international Olympic community. A majority of the number of Olympic medals won belongs to fighters from Europe, leading athletes in Asia, America and Africa. In recent years, the advantage of the European athletes has markedly decreased, which was mainly due to a substantial increase in the number of Asian wrestlers winning awards and some increase in the level of achievement of American athletes. This fact, as well as a significant expansion of the range of fighters from different countries and continents are actually competing for honors in the Olympic Games, is a powerful argument against the unfounded IOC decision calling for the exclusion of wrestling from the core Olympic sports.